Wymogi higieniczno-sanitarne w sprzedaży bezpośredniej produktów rolnych w prawie włoskim - Kapała, Anna (Wydawnictwo Naukowe UAM, 2013)
This paper aims to evaluate the use of discretionary powers in Italian legislation relating to the determination of national hygiene and sanitation measures in direct sales of agricultural products. The task undertaken was not only to determine whether national provisions have been enforced, but also to find out whether their adoption facilitates direct sales, while ensuring public health safety. The paper presents domestic measures available under Italian legislation on food sanitation applicable to different forms of direct sales. As can be seen, wherever allowed, Italian legislators introduced derogations from the EU legal provisions, especially with regards direct sales of small quantities produced according to traditional methods, also in order to adapt sanitation requirements with the local environments specifics (agro-tourism). At the same time, however, efforts have been made to ensure food safety in line with the EU recommendations.

L’articolo si propone di valutare lo sfruttamento da parte del legislatore italiano della competenza lasciatagli dalle regolazioni dell’UE al fine di determinare le misure nazionali in materia di igiene. Si tratta non solo di determinare se le regole nazionali sono state emesse, ma se esse facilitano la vendita diretta, garantendo al contempo la tutela della salute pubblica. Nell’articolo sono state affrontate più da vicino le misure previste dal legislatore italiano in materia di igiene alimentare in riferimento alla varie forme di vendita diretta. Dalle considerazioni svolte emerge che il legislatore italiano ha intrapreso nelle aree, in cui ha avuto tale opportunità, le azioni volte a introdurre eccezioni ai requisiti igienicosanitari comunitari (nell’ambito di consegne dirette di piccole quantità e di metodi di produzione tradizionali), ma anche a conciliare i requisiti dell’igiene con la specificità ambientale (attività agrituristica), avendo anche cura di garantire la sicurezza alimentare e di prendere in considerazione le direttive dell’UE.
Hygiene and sanitation requirements in direct sales of agricultural products in italian law
Requisiti igienico-sanitari nella vendita diretta dei prodotti agricoli nel diritto italiano